Characterization of a switchable chimeric antigen receptor platform in a pre-clinical solid tumor model - Bejestani, Elham Pishali; Cartellieri, Marc; Bergmann, Ralf; Ehninger, Armin; Loff, Simon; Kramer, Michael; Spehr, Johannes; Dietrich, Antje; Feldmann, Anja; Albert, Susann; Wermke, Martin; Baumann, Michael; et al. (OncoImmunology, 2017)
The universal modular chimeric antigen receptor (UniCAR) platform redirects CAR-T cells using a separated, soluble targeting module with a short half-life. This segregation allows precise controllability and flexibility. Herein we show that the UniCAR platform can be used to efficiently target solid cancers in vitro and in vivo using a pre-clinical prostate cancer model which overexpresses prostate stem cell antigen (PSCA). Short-term administration of the targeting module to tumor bearing immunocompromised mice engrafted with human UniCAR-T cells significantly delayed tumor growth and prolonged survival of recipient mice both in a low and high tumor burden model. In addition, we analyzed phenotypic and functional changes of cancer cells and UniCAR-T cells in association with the administration of the targeting module to reveal potential immunoevasive mechanisms. Most notably, UniCAR-T cell activation induced upregulation of immune-inhibitory molecules such as programmed death ligands. In conclusion, this work illustrates that the UniCAR platform mediates potent anti-tumor activity in a relevant in vitro and in vivo solid tumor model.
Gesehen am 12.08.2020